2019
DOI: 10.1111/1365-2664.13539
|View full text |Cite
|
Sign up to set email alerts
|

When to vaccinate a fluctuating wildlife population: Is timing everything?

Abstract: Wildlife vaccination is an important tool for managing the burden of infectious disease in human populations, domesticated livestock and various iconic wildlife. Although substantial progress has been made in the field of vaccine designs for wildlife, there is a gap in our understanding of how to time wildlife vaccination, relative to host demography, to best protect a population. We use a mathematical model and computer simulations to assess the outcomes of vaccination campaigns that deploy vaccines once per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…At least in Guinea and Sierra Leone, research on the population dynamics of M. natalensis indicates that density fluctuations are much weaker than those in East Africa [ 83 ]. In the case of rodent vaccination, understanding population dynamics is particularly important because distributing vaccines at seasonal population lows in wildlife demographic cycles can, in theory, substantially increase the probability of pathogen elimination [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…At least in Guinea and Sierra Leone, research on the population dynamics of M. natalensis indicates that density fluctuations are much weaker than those in East Africa [ 83 ]. In the case of rodent vaccination, understanding population dynamics is particularly important because distributing vaccines at seasonal population lows in wildlife demographic cycles can, in theory, substantially increase the probability of pathogen elimination [ 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…The demographic model includes a periodic Gaussian birth rate: b ( t ) = k exp[− σ cos 2 ( πt /365)]. Other forms of periodicity such as a sinusoidal forcing function or step function could also be used to impose seasonality [25, 26], but Peel et al [27] found broad support for a periodic Gaussian birth rate in 17 out of 18 datasets on the timing of births in wild animals. The parameter k was chosen to ensure an average population size ν :…”
Section: Methodsmentioning
confidence: 99%
“…Temporal fluctuations in population density, due to seasonal rainfall, would provide another important insight into the seasonal burden of human LF cases [11]. Understanding this ecological connection is important because distributing vaccines at seasonal population lows in wildlife demographic cycles can, in theory, substantially increase the probability of pathogen elimination [58, 59]. Incorporating these temporal layers will become more feasible as more time-series data on population density in the focal reservoir species become available.…”
Section: Discussionmentioning
confidence: 99%